Assessment of the health care waste generation rates and its management system in hospitals of Addis Ababa, Ethiopia, 2011 - Debere Mesfin Kote; Gelaye Kassahun Alemu; Alamdo Andamlak Gizaw; Trifa Zemedu Mehamed (BMC, 2013)
Abstract Background Healthcare waste management options are varying in Ethiopia. One of the first critical steps in the process of developing a reliable waste management plan requires a widespread understanding of the amount and the management system. This study aimed to assess the health care waste generation rate and its management system in some selected hospitals located in Addis Ababa, Ethiopia. Methods Six hospitals in Addis Ababa, (three private and three public), were selected using simple random sampling method for this work. Data was recorded by using an appropriately designed questionnaire, which was completed for the period of two months. The calculations were based on the weights of the health care wastes that were regularly generated in the selected hospitals over a one week period during the year 2011. Average generation indexes were determined in relation to certain important factors, like the type of hospitals (public vs private). Results The median waste generation rate was found to be varied from 0.361- 0.669 kg/patient/day, comprised of 58.69% non-hazardous and 41.31% hazardous wastes. The amount of waste generated was increased as the number of patients flow increased (rs=1). Public hospitals generated high proportion of total health care wastes (59.22%) in comparison with private hospitals (40.48%). The median waste generation rate was significantly vary between hospitals with Kruskal-Wallis test (X2=30.65, p=0.0001). The amount of waste was positively correlated with the number of patients (p < 0.05). The waste separation and treatment practices were very poor. Other alternatives for waste treatment rather than incineration such as a locally made autoclave should be evaluated and implemented. Conclusion These findings revealed that the management of health care waste at hospitals in Addis Ababa city was poor.